2012
DOI: 10.1111/j.1747-4949.2012.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Recurrent Stroke before Carotid Endarterectomy: The ANSYSCAP Study

Abstract: The risk of recurrent ipsilateral ischemic stroke was high within the first days of the presenting event. Many recurrences would likely have been avoided if carotid endarterectomy had been performed within the first days of the presenting event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 23 publications
1
57
0
Order By: Relevance
“…Table 4 summarizes the risk of early recurrent strokes in patients with symptomatic CA stenosis reported by various authors and observed in our patients. 12,18,21,23,25 The stroke risks observed by the various studies were quite variable, most likely because of differences in patient characteristics and management. Unlike in most other series, our patients had CA interventions rather early after symptom onset and admission.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 summarizes the risk of early recurrent strokes in patients with symptomatic CA stenosis reported by various authors and observed in our patients. 12,18,21,23,25 The stroke risks observed by the various studies were quite variable, most likely because of differences in patient characteristics and management. Unlike in most other series, our patients had CA interventions rather early after symptom onset and admission.…”
mentioning
confidence: 99%
“…However, in many hospitals it might be difficult to plan for very early CEAs, and the periprocedural risk of adverse events in such early operations is largely unknown. Furthermore, data to estimate the risk of recurrence of cerebrovascular events within the first 72 hours after symptom onset are scarce, 18,23,25 and only 1 of these studies has analyzed the recurrence of ipsilateral ischemic strokes. 18 Therefore, we aimed to assess the following: 1) the ipsilateral recurrence rate within 72 hours of admission, in the period from 72 hours to 7 days, and after 7 days in patients presenting with nondisabling stroke, TIA, or AF, and an ipsilateral symptomatic CA stenosis of 50% or more, and 2) the risk of stroke in CA interventions performed within 48 hours of admission compared with the risk in later interventions.…”
mentioning
confidence: 99%
“…Most Nihilists remain unconvinced about the need to deliver expedited interventions; they think that a little delay is welcome (to reduce procedural risk), and they are generally dismissive about the validity and generalizability of small studies such as the study of Marnane. However, although the scientific message of Marnane may have been the prognostic importance of macrophage inflammation, perhaps its most important role has been to corroborate 6 other contemporary, natural history studies that found that the early risk of stroke after a TIA in patients with 50% to 99% stenoses was significantly higher than previously thought (5%-8% at 48 hours, 12,13 17% at 72 hours, 14 8%-22% at 7 days, [13][14][15][16] and 11%-25% at 14 days). 13,14,17 The obvious discrepancy between a 27% stroke risk at 28 days 1 versus a 21% risk at 5 years 2 is explained by there being 2 distinct cohorts of symptomatic patient in this debate.…”
Section: Naylor You May Delay But Time Will Not 659mentioning
confidence: 55%
“…According to the recent literature, the risk of stroke recurrence is about 8-11% within the first 2 weeks for patients with SCAS [13,14], and at the same time there is evidence that early surgery in stable patients is not associated with an increased operative risk [15]. Bearing this in mind, the ambitious initial goal to operate all SCAS patients within 7-10 days has not been reached yet.…”
Section: Discussionmentioning
confidence: 99%